Rainwater for human consumption and domestic use in San Miguel Tulancingo, Oaxaca - Pérez Hernández, Aurora; Palacios Vélez, Oscar Luis; Anaya Garduño, Manuel; Tovar Salinas, Jorge Leonardo (Revista Mexicana de Ciencias Agrícolas, 2017)
The study was conducted in the municipality of San Miguel Tulancingo, Oaxaca where people use for their needs of water for human consumption and domestic use 30 L inhabitant-1 day-1. The goal was to design a system to capture rainwater to provide quality water, venough and in a continuous way to the inhabitants of the municipality. The design of the system consisted of: the location of the system at macro and micro level, the calculation of water demand, net rainfall, effective capture area, pipe diameters, sedimentation volume, storage and solar pump, to finally design the treatment train to purify the rainwater.
Keywords: water balance, rainwater collection, tank, water demand, water purification plant, net rainfall